Direct Laser Cladding of Cobalt on Ti-6Al-4V with a Compositionally Graded Interface - Jyotsna Dutta Majumdar (Advances in Materials Science and Engineering)
Direct laser cladding of cobalt on Ti-6Al-4V with and without a graded interface has been attempted using a continuous wave CO2 laser. Graded interface is developed by depositing a thin copper layer on Ti-6Al-4V substrate prior to multiple laser cladding of cobalt on it. Presence of copper interlayer was found to suppress the formation of brittle intermetallics of Ti and Co. The effect of process parameters on the microstructures, compositions, and phases of the interface was studied in details. Finally, the mechanical and electrochemical properties of the interface processed under optimum process parameters are reported.